Mauritians and Latter-Day Saints: Multicultural Oral Histories of The Church of Jesus Christ of Latter-Day Saints within “The Rainbow Nation” - Chintaram, Marie Vinnarasi (Religions, 2021)
The Church of Jesus Christ of Latter-day Saints emerged within the Mauritian landscape in the early 1980s after the arrival of foreign missionary work. With a population of Indian, African, Chinese, French heritage, and other mixed ethnicities, Mauritius celebrates multiculturalism, with many calling it the “rainbow nation”. Religiously, Hinduism dominates the scene on the island, followed by Christianity (with Catholicism as the majority); the small remainder of the population observes Islam or Buddhism. Although Mauritian society equally embraces people from these ethnic groups, it also has historically marginalized communities who represent a “hybrid” of the mentioned demographic groups. This article, based on ethnographic research, explores the experiences of Mauritian Latter-day Saints as they navigate the challenges and implications of membership in Mormonism. Specifically, it focuses on how US-based Mormonism has come to embrace the cultural heritage of people from the various diaspora and how Mauritian Latter-day Saints perceive their own belonging and space-making within an American born religion. This case study presents how the local and intersecting adaptations of language, race, and local leadership within a cosmopolitan society such as Mauritius have led to the partial hybridization of the Church into the hegemony of ethnic communities within Mauritian Latter-day Saint practices. These merging of cultures and world views prompts both positive and challenging religious experiences for Mauritian Church members. This article illustrates the implications and pressures of the Church trying to globalize its faith base while adapting its traditionally Anglocentric approaches to religious practices to multiracial, multicultural cosmopolitan communities such as Mauritius.